The Normans and empire - Bates, David 1945- (Oxford Univ. Press, 2014)
This title provides an interpretative analysis of the history of the cross-Channel empire created by William the Conqueror in 1066 to its end in 1204 when the duchy of Normandy was conquered by the French king, Philip Augustus, the so-called 'Loss of Normandy'